Design of laser-driven high-efficiency Al2O3/YAG:Ce3+ ceramic converter for automotive lighting: Fabrication, luminous emittance, and tunable color space. (April 2017) - Song, Young Hyun; Ji, Eun Kyung; Jeong, Byung Woo; Jung, Mong Kwon; Kim, Eun Young; Lee, Chul Woo; Yoon, Dae Ho
Abstract: An Al2 O3 /Y3 Al5 O12 :Ce 3+ ceramic phosphor plate (CPP) for which a nano-phosphor is used for a high-power laser diode (LD) application for white automotive-lighting is reported here. The prepared CPP shows improved luminous properties that are owing to the light propagation of the hexagonal α-Al2 O3 in the CPP. The amount of α-Al2 O3 added to the Y3 Al5 O12 :Ce 3+ CPP was optimized, and its impact on the luminous characteristics was investigated. The luminous properties of the Al2 O3 /Y3 Al5 O12 :Ce 3+ CPP are improved when compared with the Y3 Al5 O12 :Ce 3+ CPP, and the luminous emittance, as well as the conversion efficiency, is therefore also improved. The results of the present study indicate that the Al2 O3 /Y3 Al5 O12 :Ce 3+ CPP can serve as a potential material for the solid-state laser lighting in automotive applications. Highlights: Al2 O3 /Y3 Al5 O12 :Ce 3+ CPP for which a nano-phosphor is used for a high-power LD application. Al2 O3 /YAG: Ce 3+ CPP is one of the simplest ways to obtain highly luminous properties. Our material can serve as remote phosphors for phosphor-converted LDs.